Pengembangan Pembelajaran Menggunakan Media Aplikasi Quiziz untuk Menambah Minat Belajar Bahasa Jerman pada Tema Familie - Simbolon, Putri Insani; Sihombing, Stepani Veronika; Ranieri, Mehran; Rumahorbo, Ronald Febri; Pratama, Randy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of digital-based learning media on the Quizizz application to improve German language skills on a family theme includes the use of the Quizizz platform as a means to improve understanding and comprehension of German reading. This application aims to make learning German easier by providing family-themed interactive tests and exercises. The main aim of this development is to improve understanding and knowledge of the German language through a digital-based approach that allows students to learn independently and interactively.